Pelatihan dan Pendampingan Masyarakat Desa Santong dalam Membuat Pupuk Organik Cair dari Limbah Organik Pasar Tradisional - Sa’ban, Akhirul; Adam Ghifran Budiman; Rizki Hilmawan; Baiq Anggi Novita Ramadani; Eny Aulia; Nedina Huzaema; Fuji Hendra Wibawa; Kadek Widhiana Susila Pranata; Lindayani; Nur Masrurah; I Dewa Made Alit Karyawan (Universitas Mataram, 2025)
Organic waste, a byproduct of human activities, is capable of decomposing naturally. In Santong Village, the majority of organic waste originates from households, agricultural activities, and leftover food from markets. With agriculture being the primary livelihood for most residents, the accumulation of organic market waste presents an opportunity for local farmer groups to repurpose it for their own needs. This article outlines the training and assistance process for producing liquid organic fertilizer from traditional market waste and discusses its environmental, health, and economic impacts on the Santong Village community. The training and mentoring session took place at the Santong Village Office Hall on January 8, 2025, from 10:00 to 11:30 WITA. Twenty participants, including village officials, farmer groups, BUMDes representatives, the Agriculture Service, and the Santong Village Student Association, collaborated to ensure the program's sustainability. A participatory approach was employed, incorporating three primary methods: lectures, hands-on practice, and discussions. These methods facilitated better understanding among the farmer groups, enabling them to effectively grasp the materials delivered by the trainers.